A case report on antepartum and postpartum management of Wilson's disease - K. P., Bhavani Sree; R., Mangaiyakarasi; D., Tamilselvi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Wilson's disease incidence is about one in 30,000 live births. Usually occurs between the ages of 5 years and 35 years. It was described first in the year 1854 by Friedrich Theodor von Frerichs (German pathologist) and is named after Samuel Wilson (British neurologist). With our experience in this case, we are explaining the antepartum and postpartum management of a rare case of Wilson’s disease.